Ciclos de extranjerización y concentración de la tierra en Paraguay - Lorena Izá Pereira (Revista NERA, 2018)
Paraguay has the largest land concentration in the world, with the Gini index of 0.93. Concurrently, 19% of Paraguayan territory was (2008) in the possession of foreigners (CAN, 2008) and is ranked third largest exporter and sixth largest soybean producer in the world (CAPECO, 2018). In spite of this current situation, the concentration and foreignization of the land in Paraguay are configured as historical processes, since the end of the Triple Alliance War (1864-1870) and over time they become more complex, interacting even more with processes economic and political issues (ARRIGHI, 2008). In this scenario, the objective of this work is to discuss the historical process of appropriation of Paraguayan territory by foreigners from 1870 to the current period, highlighting the strategies, role of the State, geopolitical relations and impacts on the land structure of the country. Understanding this historical process is essential to understand the roots of the current concentration of land, the foreignization of the territory and the agrarian transformations that occurred in Paraguay. In order to reach this objective, in addition to a bibliographical review, we will use data from different research agencies and interviews built during fieldwork in Paraguay between the years 2015 and 2018, which allows us to reflect on the contradictions of agribusiness and the resulting impacts of land appropriation by foreigners, such as deterritorialization of peasants and indigenous peoples, insecurity and loss of food sovereignty, population increase in slums and accentuation of rural and urban poverty, which shows that the impacts from the model are beyond the rural space.